1986
DOI: 10.1007/bf01314155
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 17 isolates of the human parvovirus B 19 by restriction enzyme analysis

Abstract: The genomes of 17 isolates of the human parvovirus B 19 were compared by restriction with eight endonucleases. All but four isolates proved indistinguishable. A 3.2 kb B 19 DNA fragment was cloned and used as a molecular probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…These were all found in blood donations, with the earliest being obtained in the U.K. in 1973 and the most recent from France in 1979. The majority of the isolates mapped by Morinet et al (1986) probably fall into this group, although fewer enzyme sites were mapped by those workers. Thus a single virus genome type can remain in circulation over a 6 year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were all found in blood donations, with the earliest being obtained in the U.K. in 1973 and the most recent from France in 1979. The majority of the isolates mapped by Morinet et al (1986) probably fall into this group, although fewer enzyme sites were mapped by those workers. Thus a single virus genome type can remain in circulation over a 6 year period.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the extent of strain variation or genomic diversity of different isolates of B19 can be studied by restriction enzyme mapping. Morinet et al (1986) analysed 17 isolates with eight enzymes and found that 13 had the same map, the other four having altered sites for one or more enzyme. We have also mapped the sites where selected enzymes cut B19 DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction site polymorphism (RSP) is a convenient marker for this. Morinet et al (1986) were the first to analyse genetic variation in B19 virus strains and Mori et al (1987) analysed the genomic DNA of 48 B19 virus strains with a set of 13 restriction endonucleases (REs) recognizing six bp (6-bp REs), and grouped the strains into several genome types. There was no evident correlation between one genome type and a particular clinical manifestation of infection.…”
mentioning
confidence: 99%
“…However, some isolates obtained from patients with persistent B19 virus infection have been reported to exhibit a higher degree of variability in some parts of the genome, with the VP1 unique region being the most variable at both the DNA and protein levels with up to 4 and 8% divergence, respectively (23). Although different genome types have been described based on restriction analysis of the B19 virus genome (33,34,46,47) sequence analysis has not allowed the identification of phylogenetic clusters with well-resolved nodes within the B19 viruses (25,31).…”
mentioning
confidence: 99%